2009
DOI: 10.1111/j.1468-1331.2009.02631.x
|View full text |Cite
|
Sign up to set email alerts
|

Two different doses of Amitriptyline ER in the prophylaxis of migraine: long‐term results and predictive factors

Abstract: The prophylactic effect of amitriptyline seen in our study was rather weak and did not differ between the two treatment groups. The results of this 6-month, prospective, open-label clinical observation are therefore not encouraging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 15 publications
0
20
0
3
Order By: Relevance
“…Amitriptyline was better than placebo in reducing monthly migraine, but only in patients with depression or baseline frequent and severe migraine 93 (OR, 2.4; 95 % CI, 1.45-3.8 for every additional day of migraine at baseline). 94 No trials directly compared drug effects in patients with and without aura. Several post hoc subgroup analyses of topiramate versus placebo provided inconsistent efficacy evidence regarding aura.…”
Section: Drug Effect Modification By Select Patient Characteristicsmentioning
confidence: 99%
“…Amitriptyline was better than placebo in reducing monthly migraine, but only in patients with depression or baseline frequent and severe migraine 93 (OR, 2.4; 95 % CI, 1.45-3.8 for every additional day of migraine at baseline). 94 No trials directly compared drug effects in patients with and without aura. Several post hoc subgroup analyses of topiramate versus placebo provided inconsistent efficacy evidence regarding aura.…”
Section: Drug Effect Modification By Select Patient Characteristicsmentioning
confidence: 99%
“…26 Studies were conducted in Germany, [21][22][23] Austria, 24 Belgium, 26 the Netherlands, 27 and Brazil. 25 Dosages varied by individual patient but were within the range of approved FDA-labeled dose for migraine prophylaxis, where applicable.…”
Section: Observational Studies: Persistencementioning
confidence: 99%
“…The above studies represent the placebo‐controlled studies of amitriptyline in treatment of headache including migraine. Most studies subsequent to 1987 have been primarily comparison studies of amitriptyline vs another potential prophylactic antimigraine drug without a placebo comparison 18‐25 . These studies have generally shown that amitriptyline is comparable with or better than other known or potential prophylactic antimigraine agents.…”
mentioning
confidence: 99%